Knowledge Management for Thai SMEs Exporting Thai Local Products from Thailand to China during COVID-19 - Wu, Jiabao; Yanchinda, Jirawit (RSF Conference Series: Business, Management and Social Sciences, 2022)
Nowadays, with the development and growth of internet technology, famous Thai products can be easily purchased in China. Chiang Mai is known as the city of coffee but cannot find out where to buy it on Chinese e-commerce platforms. This research study seeks to provide as comprehensive a description as possible of the Business to the Consumer market and the current logistics of transporting coffee products between China and Thailand, use information collection, and find potential channels. The potential pattern to provide viable solutions for relevant Thai SMEs to enter the Chinese coffee bean market in the "COVID-19" pandemic condition. This research uses intelligence search to determine exported suitable coffee products from Chiang Mai, Thailand to Hangzhou, China. This research use activity-based costing to compare the cost every step and time. Find out which is the suitable logistics pattern.